Beaton and Anson Type A Classification of the Sciatic Nerve and Piriformis Complex: Clinical Considerations for Sex and Laterality - Charles R. Marchese; Aaron L. Graves; Benjamin J. Pautler; David Dye; Bradley A. Creamer; Jennifer F. Dennis (MDPI AG, 2024)
Variations of the sciatic nerve and piriformis muscle (SN-PM) relationship must be considered when discussing orthopedic procedures within the region as they may cause increased risk of SN injuries. Thirty-one formalin-embalmed, prosected donors were evaluated using the Beaton and Anson (B&A) classification system (1939). Major landmarks of the SN-PM relationship were identified, including the posterior superior iliac spine (PSIS), ischial tuberosity (IT), greater trochanter (GT), and the middle of the SN as it exits under the PM (S1). Distances measured included: PSIS-IT, PSIS-GT, IT-GT, PSIS-S1, IT-S1, GT-S1, S1-Q (distance of perpendicular line connecting S1 to PSIS-IT), and S1-R (distance of perpendicular line connecting S1 to PSIS-GT). Measurements from 49 lower extremities were evaluated using a two-tailed t-test to compare by sex and laterality; a one-tailed t-test was utilized to compare groups based on anatomical sex. Six donors displayed asymmetric B&A classifications, demonstrating gross anatomical differences within a single individual; however, no measurements were significant when comparing extremities. Seven measurements were statistically significant (p < 0.05) between sexes, indicating notable sex-based differences. These data highlight sex-based differences in the SN-PM relationship, as well as consistencies within measurements among extremities, which can be utilized by clinicians when treating male and female patients needing unilateral or bilateral orthopedic procedures or injections within the gluteal region.